Method of synthesıs novel n'-substıtuted2-((5-(thıophen-2-ylmethyl)-4h-1,2,4-trıazol-3-yl)thıo) acetohydrazıdes - Safonov, A.; Сафонов, Андрій Андрійович (My University, 2020)
The purpose of this work is to synthesize new series of N'-substituted-2-((5-(thiophen-2- ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetohydrazides.
Keywords: 1H-NMR; heterocyclic compounds; synthesis; 1,2,4-triazole